Mesenchymal stem cell-derived extracellular vesicles promote nerve regeneration after sciatic nerve crush injury in rats - Ma, Yongbin (Int J Clin Exp Pathol, 2017)
Several studies have demonstrated extracellular vesicles (EVs) derived from mesenchymal stem cells (MSCs) could promote neural regeneration following central nervous system injury. However, the therapeutic effects of MSC-EVs in peripheral nerve regeneration remain poorly understood. This study was aimed to investigate the therapeutic effects of local application of rat bone marrow mesenchymal stem cell (BMSCs) derived EVs in rat sciatic nerve crush injury model. EVs were isolated from the culture supernatants of BMSCs under serum-free conditioned medium, and identified by transmission electron microscopy (TEM) and scanning electron microscope (SEM). Then, the crush-injured segment of rat was treated by BMSC-EVs or PBS, and assessed the nerve regeneration. Results showed that BMSC-EVs size ranged from 40 to 300 nm and had a typical membrane structure under TEM and SEM. BMSC-EVs treatment promote the function recovery by sciatic function Index, improve the histomorphometric repair in nerve regeneration, and increase the expression of GAP-43, a marker for axon regeneration. The present study demonstrated that BMSC-EVs could promote the functional recovery and nerve regeneration of crush-injured sciatic nerves in rat. BMSC-EVs provide a novel cell-free therapeutic approach to peripheral nerve therapy.